2013
DOI: 10.18697/ajfand.56.11950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating diversity among Kenyan papaya germplasm using simple sequence repeat markers

Abstract: Papaya is an important fruit crop, produced in Kenya for local consumption and export. Despite a history of varietal introductions, no attempts concerned on developing varieties suited to Kenyan conditions have been documented. The objective of this study was to provide information on the diversity of germplasm available in Kenya, as a precursor to systematic plant breeding program. Forty two papaya accessions were collected from farmers' fields located in Coast, Rift Valley, Western, Nyanza, Central and Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
4
2
Order By: Relevance
“…Genetic diversity estimators revealed similar results to other genetic diversity studies using SSR markers (Asudi et al, 2013;Brown et al, 2012;Matos et al, 2013). When evaluating H o for the USDA germplasm samples, we found similar results as Brown et al (2012) which evaluated a total of 20 samples from the USDA germplasm repository and reported an H o of 0.14 (similar to 0.138 in our analysis).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Genetic diversity estimators revealed similar results to other genetic diversity studies using SSR markers (Asudi et al, 2013;Brown et al, 2012;Matos et al, 2013). When evaluating H o for the USDA germplasm samples, we found similar results as Brown et al (2012) which evaluated a total of 20 samples from the USDA germplasm repository and reported an H o of 0.14 (similar to 0.138 in our analysis).…”
Section: Discussionsupporting
confidence: 87%
“…The genetic diversity of papaya has been studied both morphologically and at a molecular level (Aikpokpodion, 2012;Alonso et al, 2009;Asudi et al, 2013;Brown et al, 2012;Matos et al, 2013;Ocampo Perez et al, 2006a;Sengupta et al, 2013;Sudha et al, 2013). Morphologically, papaya has been shown to possess great diversity (Ocampo Perez et al, 2006a).…”
mentioning
confidence: 99%
“…This average number of alleles was consistent with previous observations made by other authors, who reported averages of 4.02 (Oliveira et al 2010b) and 4.53 alleles per locus (Matos et al 2013) in the analysis of Brazilian papaya genotypes. In contrast, a higher average number of alleles per locus (6.60) was found by Ocampo Pérez et al (2007), who analyzed 72 papaya genotypes with 15 microsatellite markers, and by Asudi et al (2013), who analyzed 42 papaya genotypes from six regions in Kenya, in which 11.93 alleles per locus were observed.…”
Section: Characterization Of Minisatellite and Microsatellite Locimentioning
confidence: 88%
“…According to Asudi et al (2013), no rare alleles were found in the first study involving the genetic characterization of papaya germplasm from Kenya using microsatellite markers. These findings reinforce the importance of using molecular markers to identity and further apply strategies to preserve these rare alleles in papaya germplasm from Brazil.…”
Section: Characterization Of Minisatellite and Microsatellite Locimentioning
confidence: 99%
“…These include 'Kapoho solo' (Storey, 1969), 'Waimanalo', '77', '116', '273' from Hawaii, 'Cavite', introduced from the Philippines, '417', '418' and '455' from India, 457 from Indonesia and 'Kiru' from Tanzania. Locally developed papaya cultivars included 'Kitale', 'Malindi' and 'PP1' (Imungi and Wabule, 1990;Asudi et al, 2013). Recent evidence also indicates that various commercial cultivars such as 'US', 'Redlady', 'Sunrise', 'Sunrise-Solo' and 'Honey dew' originating from Asia and America, are regularly imported as seeds by commercial papaya growers in Kenya.…”
Section: Introductionmentioning
confidence: 99%